Indicadores para a integração da gestão das águas subterrâneas e o planejamento do uso e ocupação do solo - Ospina, Dánika Andrea Castillo (Universidade Federal de São Carlos, 2018)
Groundwater is a vital resource to the society and water ecosystem. Therefore, environmental management policies and instruments need to be directed at preserving and protecting it. However, there are current evidences of indiscriminate drilling of wells and contamination of aquifers as a consequence of landuse, final disposition of liquid and solid wastes, population density and gaps in the groundwater management. These facts are threats to the hydrological cycle and the public and environment health. Recently, groundwater policies and instruments have showed a need for an articulated approach with landuse planning and diverse studies proposed methods and thechniques where groundwater was an element in risk. Nevertheless, these studies did not contemplate guidelines for integration of groundwater management (GAS) and landuse planning (PUOS). Therefore, the goal of this work is research, analyze and suggest indicators for integration of GAS and PUOS. The research is developed by the following steps: 1) Systematic literature review (RBS), to generate information about criteria, aspects and potential indicators within an integration approach. 2) Definition of potential indicators to create an integration approach between groundwater management and landuse planning, using the criteria, principles and descriptors defined; 3) Defininition of priorities between indicators adopting an analytic hierarchy process (AHP) ; 4) Development and anyzing an indicator framework adopyting the 3S metodology and the content validity index (IVC). The results indicated that there are many tools related with monitoring, dimensioning, use intensity of groundwater and few tools about participation, normative eficiency in management groundwater and landuse planning. Despite, this information was useful to formulate an indicator framework and it has 20 principles, 64 descriptors and 45 indicators and was created with differents systematized procedures, such as, selection, analysis and validation. However, future studies are necessary for the use of the GAS and PUOS indicator framework, as well as, studies to evaluate indicators applicability in a case study with specific socioeconomic, political and environmental realities.
Indicators for integration between groundwater management and land use planning
Keywords: Águas subterrâneas; Estrutura de indicadores; Planejamento do uso e ocupação do solo; Processo analítico hierárquico; Índice de validade de conteúdo; Metodologia 3s; Indicator framework; Groundwater; Landuse planning; Analytic Hierarchy Process; Content validity index; Estructura de indicadores; Aguas subterráneas; Planeamiento del uso y ocupación del suelo; Proceso analítico jerárquico; Indice de validación de contenido; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::METODOS E TECNICAS DO PLANEJAMENTO URBANO E REGIONAL; ENGENHARIAS::ENGENHARIA SANITARIA::RECURSOS HIDRICOS::AGUAS SUBTERRANEAS E POCOS PROFUNDOS; ENGENHARIAS::ENGENHARIA SANITARIA::RECURSOS HIDRICOS::PLANEJAMENTO INTEGRADO DOS RECURSOS HIDRICOS